Online Hostel Automation - K.V, Chandrashekar; C S, Kishor kumar; B, Monisha; A, Nikitha; Appaji, Impana (IJRDO -Journal of Computer Science Engineering, 2017)
The online hostel automation system is web based software. This document is intended tominimize human works and make hostel allocation is an easier job for students and hostelauthorities by providing online application for hostel, automatically select the students from thewaiting list and mess calculation, complaint registration, notice board etc. Students will getapproval notification in their mails. Hostellers can view notice board, hostel fee and mess menu bylogging into online system. It helps to notify parents regarding their wards and their presence inhostel and their curricular will be notified to their parents using this model just in one touch and italso makes online payment and over viewing of balance fee amount easier than before. Theattendance of students or the hostellers will be recorded using bio-metric so that no duplications orcomplications will be created and it also makes easy to maintain and record about messinvestments, expenditures and details about whole hostel and hence everything will be transparentto the founder or the owner.